2020
DOI: 10.3390/antibiotics9090557
|View full text |Cite
|
Sign up to set email alerts
|

Candida auris Bloodstream Infections in Russia

Abstract: Candida auris—a fungus (yeast) that can cause hospital outbreaks was first recognized in 2009. The authors report data on 38 cases of C. auris bloodstream infections in multidisciplinary hospitals situated in two distantly located regions of Russia, considering predisposing factors, antifungal susceptibility of isolates, treatment, and outcomes. Interhospital transfers of patients and labor migration contributed to the spread of C. auris. The South Asian lineage of the studied strains was indicated by K143R su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 34 publications
2
9
0
4
Order By: Relevance
“…C. auris has previously been isolated with increasing frequency from Kuwait [ 14 , 45 ] and other Middle Eastern countries [ 22 ], and outbreaks have also been reported recently from two other (Oman and Saudi Arabia) nearby countries [ 21 , 40 , 41 ]. These reports together with our study and various outbreaks reported recently from other geographical locations [ 3 , 6 , 21 , 30 , 33 , 36 , 37 , 38 , 39 , 40 ] strongly support the emerging role of C. auris as a major cause of invasive infections and outbreaks in health care facilities worldwide that have been difficult to control. C. auris has presumably assumed this role due to several unique characteristics.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…C. auris has previously been isolated with increasing frequency from Kuwait [ 14 , 45 ] and other Middle Eastern countries [ 22 ], and outbreaks have also been reported recently from two other (Oman and Saudi Arabia) nearby countries [ 21 , 40 , 41 ]. These reports together with our study and various outbreaks reported recently from other geographical locations [ 3 , 6 , 21 , 30 , 33 , 36 , 37 , 38 , 39 , 40 ] strongly support the emerging role of C. auris as a major cause of invasive infections and outbreaks in health care facilities worldwide that have been difficult to control. C. auris has presumably assumed this role due to several unique characteristics.…”
Section: Discussionsupporting
confidence: 88%
“…Although in the beginning only sporadic cases of invasive infections due to C. auris were detected soon after its recognition as a bloodstream pathogen, nosocomial outbreaks are now being reported with increasing frequency and involving larger patient cohorts [ 10 , 11 , 28 , 31 ]. C. auris mini/major outbreaks have been reported from the United Kingdom [ 32 , 33 ], United States of America [ 34 , 35 ], India [ 12 , 16 , 25 ], Spain [ 6 , 30 , 36 ], South Africa [ 13 ], Colombia [ 37 ], Kenya [ 38 ], Russia [ 39 ], Saudi Arabia [ 40 ] and Oman [ 21 , 41 ]. Here we describe molecular epidemiology of a nosocomial outbreak which started in the high dependency unit (HDU) of a secondary-care hospital (Farwaniya Hospital) in Kuwait with genetically identical clinical and environmental C. auris isolates.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that once C. auris is introduced into a healthcare facility, it spreads rapidly among susceptible patients [ 40 , 41 ]. Thus far, C. auris outbreaks have been reported from the United States of America [ 42 , 43 , 44 , 45 ], Canada [ 46 ], Mexico [ 47 ], the United Kingdom [ 48 , 49 ], Spain [ 50 , 51 ], India [ 40 , 52 ], Pakistan [ 53 ], Russia [ 54 ], Saudi Arabia [ 55 ], Oman [ 56 , 57 ], Kuwait [ 58 ], Kenya [ 59 ], South Africa [ 60 ], and Colombia [ 61 ]. Studies describing single/multiple invasive infections and outbreaks in different countries or geographical locations in the last several years have been extensively reviewed, only some of which are cited here [ 29 , 30 , 31 , 32 , 38 ].…”
Section: Epidemiology Of C Auris Infectionsmentioning
confidence: 99%
“…Although C. auris , in addition to fungemia, has also been implicated to cause ventriculitis, pericarditis, complicated pleural effusions and intra-abdominal infections, osteomyelitis, malignant otitis/otomastoiditis, meningitis and vulvovaginitis, its role in respiratory, urinary and skin and soft tissue infections remains uncertain [ 30 , 33 , 34 , 43 , 48 , 50 , 60 , 74 , 89 , 139 , 167 , 168 ]. Due to its multidrug-resistant nature and extraordinary ability to spread rapidly in healthcare facilities causing outbreaks with associated high mortality rates [ 30 , 42 , 43 , 44 , 45 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ], the detection of even a single case of C. auris should trigger an epidemiological investigation and the implementation of infection control measures and contact precautions to prevent further transmission [ 77 , 78 , 141 ]. This requires the capacity of hospital microbiology laboratory to efficiently and correctly identify C. auris and, following the detection of positive cases, the institution of robust infection control measures which include alerting treating infectious disease specialists and notification to institutional authorities for setting up outbreak management teams.…”
Section: C Auris Infection Prevention and Control Measures In Healthcare Facilitiesmentioning
confidence: 99%
“…C. auris isolates of patients with candidemia in Russia were susceptible to echinocandins, whereas the high-level of resistance against Flu and AmB was seen in the majority of isolates. More investigation regarding surveillance might be helpful to achieve proper guidelines for the management of candidemia [ 71 ].…”
Section: Candida Auris and Treatment Failure Of Common Commercial Antifungal Drugsmentioning
confidence: 99%